Th2/Th1 Cytokine Imbalance Is Associated With Higher COVID-19 Risk Mortality - Pavel, Ana B.; Glickman, Jacob W.; Michels, James R.; Kim-Schulze, Seunghee; Miller, Rachel L.; Guttman-Yassky, Emma (Frontiers in Genetics, 2021)
A major component of COVID-19 severe respiratory syndrome is the patient’s immune response to the SARS-CoV-2 virus and the consequential multi-organ inflammatory response. Several studies suggested a potential role of CD4+ T cells in COVID-19 severe respiratory syndrome. We first hypothesized that there is a Th2/Th1 imbalance in older age, male, asthma, smokers and high ACE2 expression phenotype in the airway of non-infected patients. Next, we hypothesized that a Th2/Th1 imbalance may predict higher mortality in COVID-19 infected hospitalized patients with and without patient reported current asthma. We first analyzed publicly available gene expression from the sputum of 118 moderate-to-severe asthma patients and 21 healthy controls, and from nasal epithelium of 26 healthy current smokers and 21 healthy smokers. Secondly, we profiled 288 new serum proteomics samples measured at admission from patients hospitalized within the Mount Sinai Health System with positive SARS-CoV-2 infection. We first computed Th1 and Th2 pathway enrichment scores by gene set variation analysis and then compared the differences in Th2 and Th1 pathway scores between patients that died compared to those that survived, by linear regression. The level of Th2/Th1 imbalance, as determined by the enrichment score, was associated with age, sex, and ACE2 expression in sputum, and with active smoking status in nasal epithelium (p<0.05). Th2/Th1 imbalance at hospital admission in sera of patients was not significantly associated with death from COVID-19 (p=0.11), unless evaluated in the asthmatic strata (p=0.01). Using a similar approach we also observed a higher Th17/Th1 cytokine imbalance in all deceased patients compared to those that survived (p<0.001), as well as in the asthmatic strata only (p<0.01). Th2/Th1 imbalance is higher in the sera of asthma patients at admission that do not survive COVID-19, suggesting that the Th2/Th1 interplay may affect patient outcomes in SARS-CoV2 infection. In addition, we report that Th17/Th1 imbalance is increased in all patients that die of COVID-19.